Influence of chemicals on the growth and yield of five species of oyster mushroom ( Pleurotus spp.) in North-western Himalayas - Kumar, Ravinder; Hooda, K.S.; Bhatt, J.C.; Kumar, R. Arun (Indian Phytopathology, 2011)
Eight chemicals viz. salicylic acid (0.1%), ferrous sulphate (1%), copper sulphate (1%), manganese sulphate (1%), potassium sulphate (1%), magnesium sulphate (1%), zinc sulphate (1%) and calcium carbonate (1%) were tried to see their influence on five species of oyster mushroom ( P. sajor caju, P. florida, P. flabellatus, P. fossulatus and P. sapidus) with respect to radial growth, days for spawn run, number of fruiting bodies and yield. Maximum radial growth was observed at 6th days in ferrous sulphate and copper sulphate supplemented medium in P. sajor caju (8.56 & 9.00 cm), P. florida (9.00 & 8.75 cm), P. flabellatus (8.26 & 8.50 cm), P. fossulatus (8.45 and 8.93 cm) and P. sapidus (9.00 and 8.50 cm), respectively. Minimum time was observed for spawn run in P. sajor caju (16.33 days), P. fossulatus (16.66 days) and P. sapidus (15.00 days) supplemented with ferrous sulphate followed by magnesium sulphate (18.00, 16.66 and 16.00 days), respectively. Maximum numbers of fruiting bodies were harvested from P. sajor caju (79.95) supplemented with ZnSo4, P. florida (77.03) supplemented with salicylic acid, P. flabellatus (76.12) supplemented with CuSo4, P. fossulatus (79.91) supplemented with MnSo4 and P. sapidus (80.62) supplemented with K2So4. Yield was harvested significantly well in all the five species, P. sajor caju (602.90 g/kg), P. florida (592.10 g/kg), P. flabellatus (566.55 g/kg), P. fossulatus (604.00g/kg) and P. sapidus (612.12 g/kg) supplemented with ferrous sulphate.